Slide2.JPG Slide3.JPG

You saved atleast 2 minutes by viewing the ad-free version of this page. Thank you for being a part of Teachoo Black.


Transcript

Misc 2 Solve the inequality 6 ≤ –3(2x – 4) < 12 6 ≤ – 3(2x – 4) < 12 6 ≤ – 6x + 12 < 12 Subtracting 12 all sides (Eliminating 12) 6 – 12 ≤ – 6x + 12 – 12 < 12 – 12 –6 ≤ – 6x < 0 Dividing 6 all sides (Eliminating 6) (−6)/( 6) ≤ (−6𝑥)/6 < 0/6 −1 ≤ −𝑥 < 0 Since x is negative, we multiply both sides by -1 & change the signs (– 1) × (–1) ≥ (–1) × (–x) > (–1) × (0) 1 ≥ x > 0 0 < x ≤ 1 Thus, x is a real number which is less than or equal to 1 and greater than 0 Hence, x ∈ (0, 1] is the solution

Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science and Computer Science at Teachoo